NEW POSSIBILITIES IN PREOPERATiVE DIAGNOSIS OF NODULAR THYROID DISEASES - O. S. Olifirova (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
Galectin-3 (human Galectin-3 ELISA Bender MedSystems) was researched by the method of immune-enzyme analysis as an oncomarker in blood serum and. swabs of thyroid nodules of the patients with cancer (18) and. non-cancerous diseases of thyroid gland. (26) in the preoperative period. All the patients with thyroid cancer had. galectin-3. Average levels of galectin-3 in patients with thyroid cancer in blood serum. (0,72 ± 0,1 ng/ml) and. swabs from the thyroid, nodules (2,86 ± 0,9 ng/ml) were significantly higher than similar indices at non-cancerous diseases (0,42 ± 0,19 and 0,83 ± 0,2 ng/ml respectively). Obtained results allow to suppose the possibility of determination, of galectin-3 as an additional parameter for the complex differential diagnosis of a highly differentiated thyroid cancer by the method of immune-enzyme analysis.